KEBUDAYAAN BALI DENGAN TRADISI UPACARA NGABEN DALAM AGAMA HINDU - Salsabilla Kusumawardani, Olivia; Nadia Ayu Ardi Winata (COMMUNITY OF RESEARCH LABORATORY SURABAYA, 2022)
This study aims to describe and explain the series of local ngaben cultural implementation processes. The Ngaben Ceremony as one of the traditional cultures that contains elements of tradition has become an interesting tourist attraction for tourists, besides that as a ritual it can be said to be a tradition that is still preserved to this day. Customs, religion, and culture from the implementation of the Ngaben Ceremony can trigger the attraction of the region as a spectacle for local and foreign tourists. However, the Ngaben Ceremony always contains the meaning of luxury, because without a large cost, the Ngaben Ceremony often cannot be carried out. Therefore, not a few people carry out the Ngaben Ceremony for a long time after death. The Ngaben Ceremony is often relaxed with the purpose of the Ngaben Ceremony still being achieved. The facilities used for the implementation of the local Ngaben culture include materials from plants and animals. The implementation of the peak series of the local Ngaben culture starts from melaspas/purification of the bade and lembu, to throwing the ashes of the body into the sea.